The role of multiple high‐risk human papillomavirus infection on the persistence recurrence of high‐grade cervical lesions after standard treatment: A systematic review and a meta‐analysis - Cassani, Chiara; Dominoni, Mattia; Pasquali, Marianna Francesca; Gardella, Barbara; Spinillo, Arsenio (Acta obstetricia et gynecologica Scandinavica, 2024)
Introduction The role of multiple high‐risk human papillomavirus (HR‐HPV) infections on the occurrence of persistence/recurrence of high‐grade squamous intraepithelial lesion (HSIL) after conization/surgery for cervical intraepithelial neoplasia was evaluated. Material and methods A systematic search of Pubmed/Medine, Scopus, Cochrane databases from inception to June 30, 2023 was performed. Three reviewers independently screened the s of the selected studies and extracted data from full‐text articles. The data were subsequently tabulated and compared for consistency. The bias associated with each included study was evaluated according to the OSQE method. PROSPERO registration number CRD42023433022. Results Out of 1606 records screened, 22 full text articles met the inclusion criteria. A total of 8321 subjects treated (loop electrosurgical excision, laser or surgery) because of HSIL were followed‐up and included in the meta‐analysis. The pooled prevalence of overall persistence and/or recurrence was 17.6 (95% CI: 12.3–23.5) in multiple and 14.3 (95% CI: 10.1–19.2) in single HR‐HPV infections detected shortly before or at surgery. The pooled rate of multiple HR‐HPV infections was 25% (95% CI: 20.4–30). The odds ratio of histologically confirmed HSIL persistence and/or recurrence was significantly higher (OR: 1.38, 95% CI:1.08–1.75, p = 0.01, heterogeneity = 39%) among multiple than single HR‐HPV infections. Increased risk of HSIL persistence/recurrence was more marked among studies with multiple HR‐HPVs prevalence ≥25% (12 studies, N = 3476) (OR: 1.47, 95% CI: 1.18–1.84, heterogeneity = 0%) and in those evaluating true histologically confirmed recurrence after at least 6 months of negative follow‐up (9 studies, N = 5073) (OR: 1.67, 95% CI: 1.17–2.37, heterogeneity = 37%). Multiple HR‐HPVs infection detected during follow‐up visits had no effect on the risk of recurrence although the number of included studies was small (4 studies, N = 1248) (OR: 0.98, 95% CI: 0.68–1.39, heterogeneity = 0%). The risk of bias was rated as high in 10 and low‐moderate in 12 studies, respectively. In subgroup analysis, the risk of bias of the included studies (low/moderate vs. high), had a small, although not significant effect on the odds ratios of persistence/recurrence of HSIL (OR: 1.57, 95% CI: 1.23–2 for low‐moderate risk of bias and OR: 1.06, 95% CI: 0.65–1.75 for high risk of bias; p‐value for subgroup differences = 0.17). Conclusions Multiple HR‐HPVs infections at the time of standard treatment of HSIL entail a small but significant increased risk of persistence/recurrence of HSIL and should be taken into account in the follow‐up plan. Multiple HR‐HPVs infection among women treated for HSIL is common, involving 25% of the subjects, and is associated with a small but significantly increased risk of persistence/recurrence of high‐grade cervical lesions. In the future multiple HR‐HPV infections should be considered into the follow‐up strategy of women treated for HSIL.